The determinants of capital structure and stock returns (the KOMPAS 100 index) - Stefani Chandra., Teddy Chandra, Martha Ng, (Opción, 2019)
This research aims to test the influence of capital structure on stock returns and to analyse the factors that affect capital structure and stock returns. The sample includes firms listed on the Kompas 100 index. By using a purposive sampling technique, 64 firms were selected. This study shows that capital structure and all exogenous variables have no significant influence on stock returns. Profitability and growth opportunity have a significant negative influence on capital structure, while tangibility and liquidity have a positive influence on capital structure. Additionally, firm size and volatility do not have a significant influence on capital structure.